2004
DOI: 10.2527/2004.82113321x
|View full text |Cite
|
Sign up to set email alerts
|

Cubicle housing systems for cattle: Comfort of dairy cows depends on cubicle adjustment1

Abstract: Housing is important for the welfare of cows. Although recommendations have been proposed, abnormal movements and injury problems are still observed in cubicle houses. We conducted a survey on 70 French dairy farms that used cubicles. We examined the design of the cubicles, and the behavior, injuries, and cleanliness of the cows. Most of the cubicles did not comply with the recommendations, often being too narrow and/or too short. Difficulties in lying behavior and injuries were more common when the neck rail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 18 publications
8
63
2
2
Order By: Relevance
“…Despite the wide range of different conditions covered by the three sub-data sets, ranges within each sub-data set were in general close or equal to the range of the complete data set and comparable to other studies. Kielland et al (2009), for example, found a range of 0% to 100% for a combination of H, S and W at the carpal joints, with a mean herd prevalence of 35% for the left as well as for the right carpus, and Veissier et al (2004) a range of 0% to 100% for severe injuries, defined as open wounds or oedema, with a mean of 41%. Despite comparable prevalence ranges, mean prevalences reported are lower than median values in our study (S 83%, H 48%, W 16%), which might partly be due to the fact, that prevalences were given for each leg, separately (Kielland et al, 2009) or for severe injuries (Vessier et al, 2004).…”
Section: Distribution Of Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wide range of different conditions covered by the three sub-data sets, ranges within each sub-data set were in general close or equal to the range of the complete data set and comparable to other studies. Kielland et al (2009), for example, found a range of 0% to 100% for a combination of H, S and W at the carpal joints, with a mean herd prevalence of 35% for the left as well as for the right carpus, and Veissier et al (2004) a range of 0% to 100% for severe injuries, defined as open wounds or oedema, with a mean of 41%. Despite comparable prevalence ranges, mean prevalences reported are lower than median values in our study (S 83%, H 48%, W 16%), which might partly be due to the fact, that prevalences were given for each leg, separately (Kielland et al, 2009) or for severe injuries (Vessier et al, 2004).…”
Section: Distribution Of Alterationsmentioning
confidence: 99%
“…Mülleder and Waiblinger, 2004;Veissier et al, 2004;Kielland et al, 2009). They reflect an impairment of the cows' welfare as wounds and swellings may be painful, and alterations including hairless areas reflect repeated conflicts of the cow with its environment.…”
Section: Introductionmentioning
confidence: 99%
“…PCA have been successfully used on subsets of variables related to the same welfare issue. For instance, Veissier and Capdeville (2004) considered three main criteria describing the comfort of cows cubicles: difficulties in lying down and getting up movements, injuries, cleanliness. For each criterion, several measures were defined, a PCA was run on the data obtained from a survey on 70 farms, and the first component of PCA was considered as a summary variable to compare several cubicle designs.…”
Section: Sum (Or Mean) Of Scoresmentioning
confidence: 99%
“…principal components) are calculated to summarise the variability between observations. This approach provides the ability to describe and compare observed situations (as in Veissier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the building aspect indicators barn characteris- tics have been considered, and the indicator with the greater weighted score concerns the adequacy of the resting area, considering that the cows require approximately 10 h/d lying or resting time (Grant and Albright, 2001). The judgment of the adequacy of resting area has been obtained comparing the actual cubicle dimensions, considering the estimated live weight of lactating cows, with the standards proposed by McFarland (2003) and the indications of Veissier et al (2004). However, further indicators of the space availability aspect are the total area available per each animal and the area available for resting (number of cubicles per animal or area available per animal).…”
Section: The Indirect Indicators: Environmentmentioning
confidence: 99%